Inflammation as a Link between Obesity and Metabolic Syndrome - Faloia Emanuela; Michetti Grazia; De Robertis Marco; Luconi Maria Paola; Furlani Giorgio; Boscaro Marco (Journal of Nutrition and Metabolism)
The metabolic syndrome is a complex of clinical features leading to an increased risk for cardiovascular disease and type 2 diabetes mellitus in both sexes. Visceral obesity and insulin resistance are considered the main features determining the negative cardiovascular profile in metabolic syndrome. The aim of this paper is to highlight the central role of obesity in the development of a chronic low-grade inflammatory state that leads to insulin resistance, endothelial and microvascular dysfunctions. It is thought that the starting signal of this inflammation is overfeeding and the pathway origins in all the metabolic cells; the subsequent increase in cytokine production recruits immune cells in the extracellular environment inducing an overall systemic inflammation. This paper focuses on the molecular and cellular inflammatory mechanisms studied until now.